A Proteomic Analysis Indicates That Oxidative Stress Is the Common Feature Triggering Antibiotic Production in Streptomyces coelicolor and in the pptA Mutant of Streptomyces lividans - Lejeune, Clara; Sago, Laila; Cornu, David; Redeker, Virginie; Virolle, Marie-Joelle (Frontiers in Microbiology, 2022)
In most Streptomyces species, antibiotic production is triggered in phosphate scarcity and repressed in phosphate proficiency. However, the model strain, Streptomyces coelicolor, escapes this general rule and produces the polyketide antibiotic, actinorhoddin (ACT), even more abundantly in phosphate proficiency than in phosphate limitation. Previous studies demonstrated that ACT has “anti-oxidant” properties suggesting that its biosynthesis is triggered by oxidative stress. Interestingly, Streptomyces lividans, a strain closely related to S. coelicolor, does not produce ACT in any phosphate condition whereas the pptA/sco4144 mutant derived from it produces ACT but only in phosphate limitation. These three strains were grown in conditions of low and high phosphate availability and a comparative quantitative analysis of their proteomes was carried out in order to define the potentially common features of the ACT producing strains. The abundance of proteins of numerous pathways differed greatly between S. coelicolor and the S. lividans strains, especially those of central carbon metabolism and respiration whereas the S. lividans strains had rather similar proteins abundance for most pathways, except for enzymes involved into NAD(P)(H) metabolism. NADP results from the phosphorylation of NAD by a polyphosphate or ATP dependent NAD kinase. NADPH is necessary to fight oxidative stress since it is a co-factor of thioredoxin reductases. PptA belongs to the Pho regulon. It is an accessory protein forcing polyphosphate into a conformation allowing their efficient use by various enzymes taking polyphosphate as donor of phosphate and energy, including NAD kinase. In condition of phosphate limitation, the phosphorylation of NAD into NADP would mainly rely on polyphosphate. It would be inefficient in the pptA mutant resulting into low NADP(H) availability and thus high oxidative stress. In S. coelicolor, the high and dysfunctional respiratory activity of this strain would generate abundant reactive oxygen/nitrogen species whereas its weak glycolytic activity resulting into low carbon flux through the Pentose Phosphate Pathway, will generate insufficient levels of NADPH to combat high oxidative stress. Altogether our results indicated that high oxidative stress is the common feature triggering ACT biosynthesis in these two ACT producing strains.